2012
DOI: 10.1103/physreva.86.021602
|View full text |Cite
|
Sign up to set email alerts
|

Formation of ultracold fermionic NaLi Feshbach molecules

Abstract: We describe the formation of fermionic NaLi Feshbach molecules from an ultracold mixture of bosonic 23 Na and fermionic 6 Li. Precise magnetic field sweeps across a narrow Feshbach resonance at 745 G result in a molecule conversion fraction of 5% for our experimental densities and temperatures, corresponding to a molecule number of 5 × 10 4 . The observed molecular decay lifetime is 1.3 ms after removing free Li and Na atoms from the trap. The preparation and control of ultracold atoms has led to major advance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 39 publications
0
73
0
Order By: Relevance
“…(6). A simple choice of the single-particle states ϕ α (r) is provided by the plane waves complying with PBC in the box of size L. The wave vectors k α , α = 1, .…”
Section: A Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). A simple choice of the single-particle states ϕ α (r) is provided by the plane waves complying with PBC in the box of size L. The wave vectors k α , α = 1, .…”
Section: A Methodsmentioning
confidence: 99%
“…In the case of fermionic particles, the quest for ultracold polar molecules in their rovibrational ground state is actively being pursued using mixtures of 40 K 87 Rb [3,4], 23 Na 40 K [5], 23 Na 6 Li [6], and 133 Cs 6 Li [7]. The electric dipole moment of these heteronuclear molecules ranges from 0.56 D for 40 K 87 Rb to 5.5 D in the case of 133 Cs 6 Li. Another possibility to realize a dipolar Fermi gas is to bring highly magnetic atoms, with magnetic moments on the order of ten Bohr magnetons, to the regime of quantum degeneracy, as it has been successfully achieved with Dy [8] and Er [9] atoms.…”
Section: Introductionmentioning
confidence: 99%
“…It will therefore be important to design a molecule creation experiment with very careful field control. In this context it is worth noting that Zürn et al [64] have recently carried out radio-frequency spectroscopy on Li 2 molecules at fields around 800 G with a field precision of ±1 mG, which is close to 1 part in 10 6 , while Heo et al [18] achieved molecule formation in 6 LiNa, using a resonance 10 mG wide at 745 G, with active feedback stabilization of the current to achieve field noise less than 10 mG [18].…”
Section: A Rbybmentioning
confidence: 99%
“…In the latter, cold atomic clouds are subjected to time-dependent magnetic fields that convert atom pairs into molecules by adiabatic passage across zero-energy Feshbach resonances [9]. Recent years have seen substantial progress in producing ultracold molecules made up of pairs of alkali-metal atoms [10][11][12][13][14][15][16][17][18]. The molecules are left in high vibrational states and are susceptible to collisional trap loss.…”
Section: Introductionmentioning
confidence: 99%
“…For vanishing boson density, we prove that the bosonic condensate fraction reduces to the quasiparticle weight Z of the Fermi polaron studied in the context of polarized Fermi gases, unifying in this way two apparently unrelated quantities. Bose-Fermi (BF) mixtures with a tunable pairing interaction between bosons and fermions have been actively investigated in the context of ultracold gases , where the tunability of the BF interaction has been demonstrated and exploited in several experiments [23][24][25][26][27][28][29][30][31][32]. Previous work has shown that, even at zero temperature, a sufficiently strong BF attraction suppresses completely the boson condensate in mixtures where the number of bosons does not exceed the number of fermions [1,12,15].…”
mentioning
confidence: 99%